2001
DOI: 10.2209/tdcpublication.42.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rinsing with Phosphorylated Chitosan on Four-day Plaque Regrowth.

Abstract: This clinical investigation examined the effect of phosphorylated chitosan rinsing on plaque development and on the buffering capacity of plaque suspension. Three male adult subjects participated in the trial that was designed as a single blind study. Participants refrained from mechanical oral hygiene procedures during a four-day study and rinsed three times a day with 20 ml of test solutions. A wash-out period of three days was instituted between the placebo and phosphorylated chitosan rinsing period. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Belum pernah dilakukan pengujian efektifitas antimikroba dan antifungi larutan kitosan sebagai bahan perendam gigi tiruan sebagian lepasan. [10][11][12][13] Berdasarkan latar belakang dan uraian tersebut di atas maka penulis melakukan pengujian efek antifungi larutan chitosan pada resin akrilik heatcured. Chitosan memiliki sifat antifungi karena memiliki gugus aktif yang akan berikatan dengan mikroorganisme.…”
Section: Pendahuluanunclassified
“…Belum pernah dilakukan pengujian efektifitas antimikroba dan antifungi larutan kitosan sebagai bahan perendam gigi tiruan sebagian lepasan. [10][11][12][13] Berdasarkan latar belakang dan uraian tersebut di atas maka penulis melakukan pengujian efek antifungi larutan chitosan pada resin akrilik heatcured. Chitosan memiliki sifat antifungi karena memiliki gugus aktif yang akan berikatan dengan mikroorganisme.…”
Section: Pendahuluanunclassified
“…Chitosan showed antibacterial properties against oral bacterial pathogens [22][23][24][25] . Furthermore, recent studies demonstrated that water-soluble reduced chitosan, used as a mouth rinse solution, displayed an antibacterial and plaque-reducing action [26][27][28][29] . Chewing gum containing chitosan and chitosan derivatives, also effectively inhibited the growth of cariogenic bacteria in saliva [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…9 The purpose of this trial is to investigate the effect of SLS removal and the incorporation of whitening agents on the plaque inhibitory action of the paste using a well-accepted plaque regrowth model. [10][11][12] Plaque measurement There are a multitude of plaque indices available to researchers examining products or therapies, to detect, measure and describe the plaque effects of such interventions. Indices in current use generally estimate plaque quantity by either the area of tooth covered or the thickness of the plaque in the area measured.…”
Section: Introduction Dentifricementioning
confidence: 99%